2021
DOI: 10.3389/fbioe.2021.788527
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Potential of Biogenic Zinc Oxide Nanoparticles Synthesized From Swertia chirayita Leaf Extract on Colorectal Cancer Cells

Abstract: Chemotherapy side effects, medication resistance, and tumor metastasis impede the advancement of cancer treatments, resulting in a poor prognosis for cancer patients. In the last decade, nanoparticles (NPs) have emerged as a promising drug delivery system. Swertia chirayita has long been used as a treatment option to treat a variety of ailments. Zinc oxide nanoparticles (ZnO-NPs) were synthesized from ethanolic and methanolic extract of S. chirayita leaves. ZnO-NPs were characterized using UV-visible spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 55 publications
(74 reference statements)
6
20
0
Order By: Relevance
“…Among nanometal oxides, ZnO NPs are known for their antimicrobial 17 , anti-inflammatory and anticancer activity 12 , 18 , 19 . They are also used in sunscreens due to their characteristic ultraviolet ray scattering properties 20 , 21 , drug delivery 22 , 23 , and wound-healing applications 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among nanometal oxides, ZnO NPs are known for their antimicrobial 17 , anti-inflammatory and anticancer activity 12 , 18 , 19 . They are also used in sunscreens due to their characteristic ultraviolet ray scattering properties 20 , 21 , drug delivery 22 , 23 , and wound-healing applications 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The U.S. Food and Drug Administration (FDA) identifies ZnO as a so-called GRAS (= generally recognized as safe) substance 26 . Several studies have demonstrated approaches for the green synthesis of zinc oxide nanoparticles using different plant extracts 17 , 19 , 27 , 28 . However, the sea lavender plant, Limonium pruinosum (L.) Chaz., has not been reportedly used for ZnO NPs Synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the potential of anticancer activity of ZnONPs has been thoroughly investigated. ZnONPs nanoparticles have been established as an anticancer drug [19][20][21] because of their selective killing efficiency on proliferating cell lines [4,22,23]. Solanum procumbens has been extensively used in folk medicine in South East Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…The use of biodegradable polymers such as PLA, PLGA, and PCL also made it possible to reduce the effect on cell growth and development in vitro [ 57 , 86 , 88 ]. It is interesting to note that many studies have shown significant toxicity for cancer cells, while for normal cells, the degree of effect was low [ 89 , 90 ]. In general, the results of our cytotoxic studies are consistent with the reported results; the effect on cell growth and development is comparable to the use of other biocompatible materials [ 57 ].…”
Section: Discussionmentioning
confidence: 99%